The Effect of Product Quality on Consumer Satisfaction of Shopee Among Students of the Faculty of Teacher Training and Education Universitas Muhammadiyah Sumatera Utara - Dian Novianti Sitompul; Anisa (EDUCATION JOURNAL OF INDONESIA, 2025)
The rapid growth of e-commerce has transformed consumption habits, particularly among university students. Shopee, as a leading e-commerce platform, offers products with varying quality levels which significantly affect consumer satisfaction. This study aims to analyse the influence of product quality on consumer satisfaction of shopee user among studens of the Faculty of Teacher Training and Education at Universitas Muhammadiyah Sumatera Utara (UMSU) class of 2021. This quantitative research involved a sample of 80 respondents, with data collected trought questionnaires and analysed using simple linear regression with the aid of SPSS 25. The results demonstrate a positive and significant effect of product quality on consumer satisfaction. The findings suggrst that improving product quality is essential for enhancing consumer satisfaction and loyalty on e-commerce platforms.